(3fTCJgG heaghegG hfWGbgG hCgejJgGs - (3UdGM(B, (3Rjf GdOjfs ((3YeGf(B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B,s, 2004)
(3fTCI heaghe hfWGb GdMbhb GdacQjI(B- (3CgejJI GdMbhb GdacQjI(B- (3MeGjI GdMbhb GdacQjI(B- (3GdJcjja GdbGfhfj ddMbhb GdacQjI(B- (3GdJfXje GdbGfhfj ddMbhb GdacQjI(B- (3JMOjK bhGfjf GdMbhb GdacQjI(B- (3GdfghV HGdEHOGY GdYQHj(B.s
(3GdedGMb U(B.225s
Keywords: (3GdJcjja GdbGfhfjs; (3GdedcjI GdacQjIs; (3Mbhb GdJCdja hGdfTQs